2018
DOI: 10.2337/dc17-1778
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Severe Hypoglycemic Events Before and After Cardiovascular Outcomes in TECOS Suggests an At-Risk Type 2 Diabetes Frail Patient Phenotype

Abstract: These findings, showing greater risk of SHEs after CV events and greater risk of CV events after SHEs, suggest a common at-risk type 2 diabetes frail patient phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 21 publications
3
70
1
2
Order By: Relevance
“…Second, we did not identify patients with non‐severe hypoglycaemia in our study. Other studies found that non‐severe hypoglycaemia was not significantly associated with cardiovascular events or death . Third, we cannot determine the temporal relationship between severe hypoglycaemia and CV events in the same claim data.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Second, we did not identify patients with non‐severe hypoglycaemia in our study. Other studies found that non‐severe hypoglycaemia was not significantly associated with cardiovascular events or death . Third, we cannot determine the temporal relationship between severe hypoglycaemia and CV events in the same claim data.…”
Section: Discussionmentioning
confidence: 84%
“…It has been postulated that severe hypoglycaemia, rather than being a direct cause of MACE or all‐cause death events, may be an indicator of frailty and vulnerability to cardiovascular disease events. This concept is supported by analyses from the ADVANCE trial and the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) . In the ADVANCE trial, the risk of a CV event was markedly attenuated after adjusting for confounding factors, suggesting that the effects of confounders were substantial .…”
Section: Discussionmentioning
confidence: 95%
“…Hypoglycaemia is a major undesired effect of insulin therapy, and may play a role in a causal pathway between insulin therapy and risks of CVD and mortality. There is supporting evidence linking hypoglycaemia with increased risks of CVD and mortality in patients with T2DM or prediabetes, [47][48][49][50][51] but one study reported no significant relationship between severe/symptomatic hypoglycaemic events and CVD-specific/ all-cause mortality in patients with T2DM starting insulin therapy. 52 In the present study we found that the increased risks of clinical outcomes associated with insulin therapy became lower or even vanished after hypoglycaemia was adjusted for in the analyses, which provides the supporting evidence for the potential effect of hypoglycaemia on risks of CVD and mortality, and indicates the use of insulin per se may not be associated with increased risks of CVD and mortality ( Table 2, Table S7).…”
Section: Role Of Hypoglycaemia In Relationship Between Insulin Thermentioning
confidence: 99%
“…Ozempic has shown superior glucose lowering and weight loss in head‐to‐head trials against other available diabetes drugs, including Lilly's once‐weekly GLP‐1 agonist Trulicity . Final marketing authorization for Ozempic in Europe is anticipated in the first quarter of 2018. January 17, 2018: A new post hoc analysis of the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) for Merck's (Kenilworth, NJ, USA) dipeptidyl peptidase 4 inhibitor Januvia was published in the January edition of Diabetes Care . The authors found that severe hypoglycemia was associated with an increased risk for a subsequent primary endpoint event (non‐fatal myocardial infarction [MI], non‐fatal stroke, hospitalization for unstable angina, or cardiovascular death), with a hazard ratio (HR) of 1.55 (95% CI 1.06–2.28; P = 0.025).…”
Section: Company Updatesmentioning
confidence: 99%
“…A new post hoc analysis of the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) for Merck's (Kenilworth, NJ, USA) dipeptidyl peptidase 4 inhibitor Januvia was published in the January edition of Diabetes Care. 2 The authors found that severe hypoglycemia was associated with an increased risk for a subsequent primary endpoint event (non-fatal myocardial infarction [MI], non-fatal stroke, hospitalization for unstable angina, or cardiovascular death), with a hazard ratio (HR) of 1.55 (95% CI 1.06-2.28; P = 0.025). Severe hypoglycemia also increased the risk for all-cause death (HR 1.83, 95% CI 1.22-2.75; P = 0.004) and for cardiovascular death (HR 1.72, 95% CI 1.02-2.87; P = 0.040).…”
Section: January 17 2018mentioning
confidence: 99%